(untitled) (Communications in Mathematical Research, 2021)
Khovanov type homology is a generalization of Khovanov homology. The main result of this paper is to give a recursive formula for Khovanov type homology of pretzel knots P(−n, −m, m). The computations reveal that the rank of the homology of pretzel knots is an invariant of n. The proof is based on a "shortcut" and two lemmas that recursively reduce the computational complexity of Khovanov type homology.